The Relationship between Knowledge and Attitude with Behavior of Preventing Leptospirosis in Healthcare Workers at the Binjai City - Yolanda Hanalena; Evita Mayasari (Sumatera Medical Journal, 2022)
Leptospirosis is an infectious disease caused by spirochete from the genus Leptospira, namely Leptospira interrogans which is pathogenic for both humans and animals. L. interrogans infection is often associated with flooding, where L. interrogans is carried from soil contaminated with animal urine reservoirs and settles in water. Leptospirosis is estimated to cause 1030000 cases and 58900 deaths annually worldwide. Until now, Leptospirosis is still a threat to public health because it causes Extraordinary Events (KLB) in several regions in Indonesia. Leptospirosis outbreaks are related to the presence of risk factors, namely the high population of rats as reservoirs of Leptospira spp., poor environmental sanitation, and the increasing number of flood areas in Indonesia. The purpose of this study was to determine the relationship between knowledge and attitude with the behavior of preventing Leptospirosis in healthcare workers at the Sub-District Health Center, Binjai Timur, Binjai City, against Leptospirosis. This research is an analytic study with a cross sectional design. The research was conducted using a questionnaire instrument of knowledge level about Leptospirosis, attitudes towards Leptospirosis, and preventive behavior towards Leptospirosis.